Enhanced endoplasmic reticulum and mitochondrial stress in abdominal aortic aneurysm. (5th July 2019) - Navas-Madroñal, Miquel; Rodriguez, Cristina; Kassan, Modar; Fité, Joan; Escudero, José R.; Cañes, Laia; Martínez-González, José; Camacho, Mercedes; Galán, María
Abstract : Abdominal aortic aneurysm (AAA) is a degenerative vascular disease with a complex aetiology that remains to be fully elucidated. Clinical management of AAA is limited to surgical repair, while an effective pharmacotherapy is still awaited. Endoplasmic reticulum (ER) stress and mitochondrial dysfunction have been involved in the pathogenesis of cardiovascular diseases (CVDs), although their contribution to AAA development is uncertain. Therefore, we aimed to determine their implication in AAA and investigated the profile of oxysterols in plasma, specifically 7-ketocholesterol (7-KC), as an ER stress inducer. In the present study, we determined aortic ER stress activation in a large cohort of AAA patients compared with healthy donors. Higher gene expression of activating transcription factor (ATF) 6 (ATF6), IRE-1, X-binding protein 1 (XBP-1), C/EBP-homologous protein (CHOP), CRELD2 and suppressor/enhancer of Lin-12-like (SEL1L) and greater protein levels of active ATF6, active XBP1 and of the pro-apoptotic protein CHOP were detected in human aneurysmatic samples. This was accompanied by an exacerbated apoptosis, higher reactive oxygen species (ROS) production and by a reduction in mitochondrial biogenesis in the vascular wall of AAA. The quantification of oxysterols, performed by liquid chromatography-(atmospheric pressure chemical ionization (APCI))-mass spectrometry, showed that levels of 7-KC were significantly higher while those of 7α-hydroxycholesterol (HC), 24-HC and 27-HC were lower in AAA patients compared with healthy donors. Interestingly, the levels of 7-KC correlate with the expression of ER stress markers. Our results evidence an induction of ER stress in the vascular wall of AAA patients associated with an increase in circulating 7-KC levels and a reduction in mitochondrial biogenesis suggesting their implication in the pathophysiology of this disease.